2018
DOI: 10.1159/000490724
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Stroke Knowledge between Rural and Urban Communities in a Developing Country after Community-Based Stroke Educational Campaigns: Results from a Cross-Sectional Study

Abstract: Background: Ischemic stroke is a leading cause of disability and death in Mexico. Poor ability to identify signs and symptoms of ischemic stroke leads to longer hospital arrival times and precludes prompt treatment. The knowledge of stroke risk factors and warning signs in rural population is scarce. Since 2010, Stroke Education Campaigns are performed with a community-based approach. The aim of this study was to assess and compare stroke knowledge in rural and urban communities. Methods: During World Stroke C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…As for place of residence and its relationship to the level of awareness of the surveyed population, this could be explained by access to healthy lifestyle advice for the population living in urban areas, unlike that of rural areas, confirmed recently by the results of the national survey on common risk factors for non-communicable diseases [26]. On the other hand, there was a study conducted in Mexico, which suggested that due to the increased frequency of awareness and information campaigns in rural areas and due to the consolidated "physician-patient" relationship in rural primary health care centers that more preventive education on common cardiovascular disorders, such as stroke, may be found [37].…”
Section: Discussionmentioning
confidence: 82%
“…As for place of residence and its relationship to the level of awareness of the surveyed population, this could be explained by access to healthy lifestyle advice for the population living in urban areas, unlike that of rural areas, confirmed recently by the results of the national survey on common risk factors for non-communicable diseases [26]. On the other hand, there was a study conducted in Mexico, which suggested that due to the increased frequency of awareness and information campaigns in rural areas and due to the consolidated "physician-patient" relationship in rural primary health care centers that more preventive education on common cardiovascular disorders, such as stroke, may be found [37].…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have described deficits in stroke knowledge in rural populations in addition to sociodemographic factors to account for differences in behaviour [10,16]. We observed that the response to stroke symptoms was different despite similar knowledge of basic stroke principles (critical time window, the awareness that patients have a stroke).…”
Section: Comparison With Previous Studiesmentioning
confidence: 68%
“…Despite these efforts, relevant deficits in knowledge of stroke risk factors and particular stroke symptoms persist and can vary strongly in rural communities [8,9]. It is critical to understand the reasons for this knowledge gap in stroke care and study other factors that may affect prehospital delays to address these disparities effectively and improve educational campaigns in both developed and developing countries [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Dear editor: Neisseria meningitidis is a Gram-negative organism associated with serious diseases; while 13 meningococcal serogroups have been described, most cases are associated with serogroups; A, B, C, X, Y and W. 1 The General Epidemiology Department (DGE, by its acronym in Spanish) of Mexico reported 37 cases of meningococcal meningitis in 2017 (0.02 cases per 100 000 persons) and 20 cases in the first semester of 2018, none of them from the state of Nuevo León. 2,3 Between August 2018 and March 2019, our laboratory confirmed 10 cases of meningococcal infection; with eight patients from the university hospital and two from two other hospitals.…”
Section: Increased Incidence Of Neisseria Meningitidis Infections In mentioning
confidence: 86%